CURRENT STATE OF DEVELOPMENT TRENDS AND COMPETITIVENESS OF AGRICULTURE IN UZBEKISTAN - Ochilov Nazrillo Fayzilloevich (Scholar Express Journals, 2021)
The article assesses the trends in agricultural development of Uzbekistan and identifies specific features of increasing the level of competitiveness of the agricultural sector
Keywords: Agriculture; competitiveness; arable land; products